Productivity and Land Use Efficiency of Maize-Soybean Intercropping Under Different Tillage Practices at Teppi Southwestern Ethiopia - Abayneh, Behailu Mekonnen (Plantropica: Journal of Agricultural Science, 2023)
For smallholder farmers in southwest Ethiopia, maize-soybean intercropping systems offer enormous benefits. Even though there has been little research on the socioeconomic benefits of this intercropping in the region, there is still a dearth of knowledge on the ideal cropping ratio. Accordingly, a two-year field experiment was carried out at Teppi Agricultural Research Center (TARC) during the main cropping season (under rain-fed conditions), from April 2021 to January 2023, with the aim of identifying the optimum intercropping combinations with appropriate tillage practices for enhanced land use efficiency, yield, and economic advantages of maize and soybean intercropping systems. It was laid out using a split-plot design with three replications using two tillage practices (zero tillage and conventional tillage) as main plot treatments and five intercrop combinations of maize and soybean (1:0, 0:1, 1:1, 2:1, and 1:2) as sub-plot treatments. Based on the combined data analysis, the yield attributes of the component crops and competition indices were significantly (P<0.05) affected by the main effect of maize-soybean intercropping. However, the main effect of tillage practices and their interaction with intercropping had a non-significant (P>0.05) effect on the yield attributes of the component crops and competition indices. The highest harvest index, grain yield, and aboveground biomass yield of maize and soybean were obtained from each solely cropped plot, respectively. The same plots also gave the maximum values of hundred and thousand seed weights of soybean and maize, respectively. Regarding yield and economic advantage, the highest total land equivalent ratio (LER) value (1.17), area time equivalent ratio (ATER) (1.16), and monetary advantage index (MAI) (17,224 ETB ha-1) were recorded from the 2:1 maize and soybean intercrop combination. Thus, the findings of this study suggest enhanced resource use efficiency in maize-soybean intercropping, resulting in greater yield and monetary advantage over the sole cropping of the component crops. Therefore, in conclusion, the 2:1 maize and soybean intercrop combination can be suggested as the best combination for improved land use efficiency, yield, and economic advantage in comparison with other combinations. However, prior to recommendation, the study needs to be carried out for more than two growing seasons with the inclusion of minimum tillage practices to point out the effects on maize and soybean yield, production cost, and biological and physico-chemical properties of the soil in the long run.